Constructing A Framework on Corruption Using a Matrix of Economic Freedom and Institutional Governance: Evidence from Asia Pacific (S/O 21124) - Mohd Rashid, Rasidah
The main objective of this research is to examine the impact of economic freedom on corruption in order to identify the most influential factors that should be emphasised in reducing corruption in Asia-Pacific countries. Furthermore, this study explains the intensity of corruption in Asia-Pacific countries by using institutional quality as an interaction variable between economic freedom and corruption. This study used pooled OLS regression, as well as GMM-Dynamic Panel and 2SLS for the robustness test, on data on 41 Asia-Pacific countries from 2013 to 2021. The findings demonstrate that fiscal health, government spending, property rights, government integrity, trade freedom, financial freedom, and labour freedom have a negative impact on the intensity of corruption in Asia-Pacific countries. Further, a country’s institutional quality has a significant positive interaction effect on the relationship between government size and corruption. The results are consistent with GMM and 2SLS findings. In their effort to combat corruption, policymakers should strive to promote a corruption-free image for the country by fostering a stable economic and political climate and ensuring macroeconomic stability through increased economic freedom. The findings indicate that increased economic freedom is significantly linked to healthier societies, better environments, higher per capita wealth, human growth, democracy, and poverty eradication. Prior research focused on developed and developing countries, such as ASEAN and South Asian countries, leaving Asia-Pacific countries largely unexplored regarding the relationship between economic freedom and corruption.